Using Commonplace Books to Enrich Medieval and Renaissance Courses. - Parker, Sarah E. (Teaching the Medieval Ages - ARC Series, 2023)
Covering a variety of methods for introducing students to the medieval and Renaissance reading practice known as commonplacing, this volume provides instructors with concrete guidelines for using commonplace books as a teaching and learning tool.